Effects of shank mass manipulation on landing and takeoff techniques in sprinting - Zhang, C.; Yu, B.; Liu, Y. (ISBS Proceedings Archive (Michigan), 2018)
The purpose of this study was to determine the effects of shank mass manipulation on landing and takeoff techniques in maximal speed sprinting. Sixteen male sprinters sprinted without and with an additional 15% shank mass attached around the center of mass of shank. Kinematic data in maximal speed phase were collected, reduced, and analyzed using linear regression analyses with category variable and paired t-tests. The sprinting speed and knee joint angle at landing were significantly decreased with 15% shank mass manipulation. The 15% shank mass manipulation did not significantly affect the relationships of sprinting speed with critical linear and angular kinematics at landing and takeoff of maximal speed sprinting. These results suggest that the additional 15% shank mass does not change landing and takeoff sprinting techniques of male sprinters in maximal speed sprinting.